Morphological analysis of soil particles at multiple length-scale reveals nutrient stocks of Amazonian Anthrosols - Oliveira, Naiara C.; Paschoal, Alexandre R.; Paula, Ricardo J.; Constantino, Isabela C. [UNESP]; Bisinoti, Marcia C. [UNESP]; Moreira, Altair B. [UNESP]; Fregolente, Lais G. [UNESP]; Santana, Ariane M. [UNESP]; Sousa, Francisco A.; Ferreira, Odair P.; Paula, Amauri J. (Elsevier, 2018)
We have imaged the particles of Brazilian soils at multiple length scales, from a few microns to millimeters, and soil particle size distributions were calculated with unmatched precision. The analysis included the Amazonian soil “Terra Mulata de Índio” (TMI), an anthropogenic soil (Anthrosol) with sustained fertility and a large amount of stabilized organic matter. Firstly, the soils were imaged ex situ, without any chemical processing, with sequential electron scanning of the pelletized soil samples, covering a total area of 8 × 8 mm. Secondly, it was performed a computational analysis of the large-field X-ray images assembled from hundreds of adjacent elemental maps, thus resulting in high-definition images (4800 × 4800 pixels). This analytical approach provides a large sampling with the identification of > 10,000 particles over the scanned area. The particles identified consisted of Al, C, Ca, Cr, F, Fe, Mg, Mn, Na, O, P, S, Si and Ti. A significantly larger concentration of C-, Ca- and P-based particles, of up to 100 μm2 of cross-section area, was found in TMI samples in comparison with oxisol and ultisol soils. While the mean distance between neighboring C, Ca and P particles in TMI was of 40–70 μm, the value was of hundreds of microns in oxisol and ultisol. Furthermore, mapping of micrometric carbon particles by Raman spectroscopy indicated that they have a graphitic structure with a large amount of defects, partially associated with particle oxidation, although a well-preserved sp2 graphitic structure is also present. From a technological perspective, improved soil amendments, such as biochar, can be rationally designed from the “fingerprint” described here for soil particles of Amazonian Anthrosols (i.e., morphological and structural characteristics), which can result in an increase in fertility and the optimization of carbon sequestration in the future.
Keywords: Carbon sequestration; Soil amendments; Sustained fertility; Terra Mulata de Índio; Terra Preta de Índio; X-ray energy dispersive spectroscopy